A study of experiential learning features in two departments at Haifa University International School: Jewish Studies and Israel Studies - Mayer, Gabriel (Advances in Social Sciences Research Journal, 2018)
This study examines the student cohorts of the Haifa University International School departments of Jewish Studies and Israel Studies. Specifically addressed will be subject content that is not directly named or expressed within the curricula of courses offered, but nonetheless constitutes approximately 25%-30% of student course time. These are experientially guided encounters dispersed throughout the multiple courses offered, but while unique, this aspect of learning has hitherto remained unidentified, not quantitated, nor in any manner recognized as a significant teaching and learning experience. Underlying the students’ encounter with these programs are issues of culture and identity. One way of saying this would be, the study of a moment when Jewish [Israel] peoplehood meets a transnational peoplehood. One of the basic elements guiding the study is the long held belief and conviction that Israel is the land of the Jews from Biblical times onward. Thus the visiting of many sites, monuments, landmarks and even settlements-old and new-is a uniquely different experience from similar activities in other programs and other countries. Here in these study programs which are all within the scope of the discipline of history, the students gain a palpable encounter with their subject matter and during their stay in Israel they are experiencing an annual cycle of holidays and festivals that conform to biblical history as well as the nation building narrative of their host land.